CAUSES OF THE INCREASING INCIDENCE OF SEXUALLY TRANSMITTED INFECTIONS IN WOMEN AND PREVENTIVE MEASURES - Yuldasheva Barnoxonim; Rahmatullayeva Aziza Farhodovna (PEDAGOGS, 2025)
Annotation: This scientific article analyzes the importance of modern screening and colposcopic examinations in the early detection of cervical cancer among women. The research was conducted at the Department of Obstetrics and Gynecology, Alfraganus University, between 2022 and 2025, involving 150 women aged 18–55. Cervical epithelial morphology and function were assessed based on PAP-smear, HPV (Human Papillomavirus) testing, and colposcopy results. Findings showed that early-stage screening enabled the timely detection of dysplasia and oncopathologies in 78% of cases. Approaches based on WHO (2023) and CDC (2024) recommendations confirmed the effectiveness of preventive screening programs.